The Mediating Role of Trust in the Impact of Electronic Word of Mouth (E-WOM) and Sales Promotions on Purchase Decisions in Shopee E-Commerce among Urban Consumer - Yurizal, Shalsabila Azzahra Putri; Purwanto, Edi (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2024)
Electronic Word of Mouth (eWOM) and sales promotion are critical factors influencing consumer behavior, particularly in the digital age. While previous studies have identified the impact of these factors on Trust, there is a need for a more comprehensive understanding of their roles in the consumer decision-making process. This study explores the relationships between Electronic Word of Mouth (EWOM), Sales Promotion, Trust, and Purchase Decisions in e-commerce. Utilizing structural equation modeling (SEM) with data from online consumers, the research demonstrates that EWOM and Sales Promotion significantly impact Trust, significantly influencing Purchase Decisions. The findings confirm that all constructs exhibit high reliability and validity. The study contributes to the existing literature by highlighting the mediating role of Trust between EWOM, Sales Promotion, and Purchase Decisions. From a policy perspective, ensuring transparency and authenticity in online reviews and sales promotions is crucial for maintaining consumer trust. E-commerce platforms like Shopee should enhance verification processes and leverage social media for effective promotional strategies. Businesses are advised to build Trust through high-quality products, excellent customer service, and transparent communication. This research reinforces the importance of EWOM and Sales Promotion in building consumer trust, which is essential for driving purchase decisions and achieving better market performance.